Effects of feed supplementation with glycine chelate and iron sulfate on selected parameters of cell-mediated immune response in broiler chickens. (August 2016) - Jarosz, Łukasz; Kwiecień, Małgorzata; Marek, Agnieszka; Grądzki, Zbigniew; Winiarska-Mieczan, Anna; Kalinowski, Marcin; Laskowska, Ewa
Abstract: Because little is known about the impact of chelated (Fe-Gly, Fe-Gly + F) and inorganic (FeSO4, FeSO4  + F) iron products on immune response parameters in broiler chickens, the objective of the study was to determine the effects of inorganic and organic forms of iron on selected parameters of the cell-mediated immune response in broiler chickens by assessing the percentage of CD3 +  CD4 +, CD3 +  CD8 +, CD25 +, and MHC Class II lymphocytes, as well as the CD4 + /CD8 + ratio and IL-2 concentration in the peripheral blood. The experiments were conducted using 50 day-old Ross 308 roosters. The test material was peripheral blood. Flow cytometry was used to determine selected cell-mediated immune response parameters. The results obtained indicate that the use of iron chelates in the diet of broiler chickens may stimulate cellular defense mechanisms. As a result of the experiment an increase was observed in the percentage of Th1, mainly T CD4 + and T CD8 + . It was also noted that application of chelated iron can increase production of T CD8 + cytotoxic cells and IL-2, which promotes the body's natural response to developing inflammation. There were no changes in T CD4 +, T CD8 +, T CD25 + or MHC II lymphocyte subpopulations in the chickens following application of the inorganic form of iron. Highlights: Iron chelate stimulates Th1 lymphocytes being cell-mediated response inducers. Iron chelate increases the percentage of cells with CD4 +, CD8 +, CD25 + expression. Iron chelate increases the percentage of T lymphocytes with Il-2 receptor. Iron chelate as a feed additive activates cytotoxic T lymphocytes in chicken.